2009
DOI: 10.1029/2009gl038581
|View full text |Cite
|
Sign up to set email alerts
|

Estimating biomass consumed from fire using MODIS FRE

Abstract: [1] Biomass burning is an important global phenomenon impacting atmospheric composition. Application of satellite based measures of fire radiative energy (FRE) has been shown to be effective for estimating biomass consumed, which can then be used to estimate gas and aerosol emissions. However, application of FRE has been limited in both temporal and spatial scale. In this paper we offer a methodology to estimate FRE globally for 2001 -2007 at monthly time steps using MODIS. Accuracy assessment shows that our F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 23 publications
2
92
2
Order By: Relevance
“…The total biomass consumed by fire is linearly related to the temporal integration of FRP over the fire duration and has been estimated from satellite by summing, or averaging, FRP over large (0.5-1°) geographic grids Roberts and Wooster 2008;Ellicott et al 2009;Kaiser et al 2012) or over satellite mapped burned areas . As the different fire types are expected to consume different amounts of biomass, particularly the deforestation and maintenance fire types, the summed FRP for 365 days prior to the active fire detection was derived within a 1 km buffer around the center of the active fire pixel location (SumFRP365d, Table 1).…”
Section: Fire Radiative Powermentioning
confidence: 99%
“…The total biomass consumed by fire is linearly related to the temporal integration of FRP over the fire duration and has been estimated from satellite by summing, or averaging, FRP over large (0.5-1°) geographic grids Roberts and Wooster 2008;Ellicott et al 2009;Kaiser et al 2012) or over satellite mapped burned areas . As the different fire types are expected to consume different amounts of biomass, particularly the deforestation and maintenance fire types, the summed FRP for 365 days prior to the active fire detection was derived within a 1 km buffer around the center of the active fire pixel location (SumFRP365d, Table 1).…”
Section: Fire Radiative Powermentioning
confidence: 99%
“…Even if a fire is detected by a polar-orbiting sensor, the overpass schedule coupled with variations in sensor scan angle will inevitably limit and confound a reconstruction of the fire's diurnal cycle [6,7]. Although several methods have been developed to overcome the inability of a polar orbiting sensor to characterize the full diurnal cycle of fire activity (e.g., [8][9][10][11]) these techniques require the accumulation of active fire pixels into large spatiotemporal windows to produce "aggregate" or "average" diurnal cycles representative of broad geographical regions and entire fire seasons. Although such generalized diurnal cycles of fire activity may be indicative of synoptic scale land use practices and meteorology, an "aggregate" or "average" diurnal cycle may not represent any particular event since fires at finer spatiotemporal resolutions are increasingly influenced by the actual timing of ignition and the local weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…greater number of detections near nadir and decreasing detections with scan angle). With regards to the application of FRE-based biomass consumption estimates published by Ellicott et al (2009) and Roberts & Wooster (2008), there is some degree of uncertainty.…”
Section: Uncertaintymentioning
confidence: 99%
“…Finally, an error budget provided by Vermote et al (2009) suggested that the FREparameterization approach developed by Ellicott et al (2009) approaches 20% based on comparisons with the SEVIRI sensor.…”
Section: Uncertaintymentioning
confidence: 99%